The Effectiveness of Capture The Flag as a Network Security Practical Intervention on Students' Self-Efficacy and Learning Outcomes - A. St.Khadijah Ridwan; Ummu Radiyah; Muhammad Ihksan Malik; Muhammad Nauval Pattiroi; Muslika; Nining Ulul Fajri; Nirwana Amir (Information Technology Education Journal, 2025)
This study aimed to evaluate the effectiveness of Capture the Flag (CTF) competitions in improving self-efficacy and learning outcomes in network security education. Specifically, it explored whether participation in CTF competitions enhances students' confidence in their cybersecurity abilities and their understanding of network security concepts compared to traditional practical exercises. A quasi-experimental design was used with 60 undergraduate students enrolled in a network security course. Participants were randomly assigned to an experimental group (CTF competition) and a control group (traditional practical exercises). Data were collected through pre-test and post-test measures of self-efficacy, a final exam, and a practical skills assessment. The experimental group participated in a two-week CTF competition, while the control group engaged in structured, instructor-guided exercises. The results indicated that the experimental group showed a significant increase in self-efficacy (from 3.2 to 4.0) and performed better on both the final exam (85% vs. 75%) and the practical skills assessment (88% vs. 78%) compared to the control group. These findings suggest that CTF competitions positively impact students’ confidence and technical skills in network security. The study’s quasi-experimental design limits the ability to draw causal conclusions. Additionally, the relatively small sample size and single-institution setting reduce the generalizability of the findings. Future studies with larger and more diverse samples are needed to confirm these results. This study contributes to the growing body of research on gamification in cybersecurity education, showing that CTF competitions can effectively enhance both self-efficacy and learning outcomes. It highlights the value of integrating such competitions into curricula to improve student engagement and preparedness for real-world cybersecurity challenges